AWARENESS OF NANOTECHNOLOGY AMONG STUDENTS OF THE COLLEGE OF BASIC EDUCATION AT THE UNIVERSITY OF DIYALA - Bushra Khairallah Ahmed; Dr. Majed Abdel Sattar Abdel Karim (Journals Park Publishing, 2022)
Aim to search Present Identify on me "Awareness with technology nano I have students College of Basic Education at the University of Diyala"adopted researcher curriculum descriptive Analytical, the study associative, and to achieve Goals search Lost It was completed Preparation Scale Awareness with technology nano, and be the society From students(College Education the basic–Department of Science) for the year school(2021-2022)and the adult their number(161)Student female student, so did researcher apply a tool the study on them distance making sure From honesty and constancy, Done Use packet stats(SPSS), to analyze the data and extract the results, and the search results showed the following: -• That students Division Sciences in Education the basic no they own Awareness with technology Nano.
Keywords: awareness; nanotechnology